A Mediated Moderation Analysis Of The Efficacy Of E-Hrm - Javad Shahreki; Anahita Ghanad (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The aim of this paper is to examine the effectiveness of e-HRM by a mediated moderation analysis. This paper used both descriptive and quantitative approaches, while the research unit of analysis consists of Line managers and HR specialists. Purposeful sampling was used for the sampling process in this study while, the research sample consists of 373 Line managers and HR specialists. A questionnaire was used to collect data and PLS-SEM was used to evaluate the study. This study responds to two concerns raised in earlier e-HRM studies; first, to draw attention to the importance of the connection between technology and organisational features; and second, to indicate that the implementation of e-HRM leads to higher-quality HRM services. The main factors affecting the excellent quality of HRM services are the benefits of both traditional HRM and e-HRM. Repeated use of e-HRM and user guidance confirmed their mediating effect, while appropriation of e-HRM and acceptance of the e-HRM system demonstrated their moderating influence. This paper encourage line managers and HR specialists must ensure that e-HRM systems are user-friendly and understandable to the intended audience (e.g. Operational: e-payroll processes, Relational: e-recruitment and selection, Transformational: online talent management). This paper has made a significant contribution to knowledge and to the operationalization of e-HRM literature, which could help to develop theory, model, practice and research in areas of HRM quality of service.